Behavioral Cognitive Therapy to Reduce Depression Symptoms: Terapi Kognitif Perilaku Untuk Mengurangi Gejala Depresi - Safira, Tia (Psikologia : Jurnal Psikologi, 2019)
The client is a 37-year-old woman who experiences symptoms of depression. The assessment is carried out on the client in the form of observation, interviews, giving graphic tests, TAT, and WAIS. The results of the assessment indicate that the client is experiencing symptoms of depression. The intervention given was cognitive behavioral therapy which was arranged in 9 therapy sessions. The purpose of this intervention is to reduce depressive symptoms in the form of crying behavior, difficulty concentrating, and difficulty sleeping. The result of this intervention is that symptoms of client depression can be reduced, effectively reduce negative thoughts, and actively and productively carry out activities that have been arranged related to social activities in which there are interactions with others.